Research on international Cultural Heritage Management of Taijiquan from the perspective of World Intangible Cultural Heritage - Liu, Yimeng (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: A vein of wenxin generation. Taijiquan has long been steeped in Chinese culture, spanning regions and classes, and has had a lasting and far-reaching impact on the development of human history. This paper takes the world intangible cultural heritage as the perspective, follows the historical form of cultural heritage circulation, and seeks to promote a community with a shared future for mankind. It focuses on the construction of international cultural discourse and national identity, and explores the management of international cultural heritage suitable for China's national conditions. Explore taijiquan in the international cultural heritage management globalization and modernization of China, and the tension between tradition and balance, emphasis on the heritage protection, management and development in the process of the integrity of ecological space and inheritance of the evolution of traceability, reasonable authorized taijiquan as the value of cultural heritage at the international space production, in order to realize the tai chi chuan the original true replication inheritance and preservation, To form a long-term and effective working mechanism for international cultural heritage management, and to provide constructive suggestions for promoting the protection and management of intangible cultural heritage in the international community. Methods: Literature, historical analysis and logical analysis were used. Results: Promoting cultural heritage undertakings represented by Taijiquan is an important measure to gradually enhance China's international cultural discourse power and the country's deep participation in global public service governance. It is a powerful driving force for building a community with a shared future for mankind and an important means for China to build a new theoretical system of international relations. In 2020, Tai Chi was included in the UNESCO World Heritage List as a World Heritage. Tai Chi has an outstanding cultural heritage and contains high humanistic value. Since China acceded to the World Heritage Convention in 1985, 55 items have been declared as world intangible cultural heritage, ranking first in the total number of World heritage sites. As one of the fastest increase in the number of world heritage in the world, China in the international cultural heritage management research has achieved great progress, such as: (1) the management mechanism, to explore the natural heritage is established based on natural protected area management mechanism, strengthening the construction of the conservation and management level, realize the science of the world heritage protection and effective regulation. (2) Benefit people's livelihood: Adhere to the ecological service for people, scientific utilization, combine resource protection with people's livelihood development, and benefit people and improve through franchising, benefit sharing, ecological compensation, living subsidies and other ways. (3) Cultural exchange: It has effectively enhanced the cultural identity of different countries, ethnic groups and beliefs, and promoted exchanges and mutual learning among civilizations. (4) Heritage restoration: The ecological protection and restoration of the heritage sites have been strengthened to maintain the integrity and authenticity of the heritage sites. Tai Chi acts on human society in the form of vitality. Human through the production practice of the meanings and the wisdom of Chinese traditional philosophy contains martial art forms of memory symbols, simplified routines as a carrier for memory storage, the Chinese traditional philosophy thought and the core technique of pure and Jane refined into a combination of offensive and defensive consciousness action programming complete set of movements, in the "pass-by-pass" to parse and extract of Chinese culture and human civilization, Finally formed the indelible human civilization skills. Therefore, we should maintain confidence and resolve in our own culture, adhere to the principle of harmony without uniformity, and carry out exchanges and cooperation based on inclusiveness. We should maintain an open global perspective and learn from the excellent achievements of other civilizations, so as to tell the story of Chinese history to the world, explain the Spirit of the Chinese nation, and build the image of a great civilized country. Conclusion: International heritage management was initiated in Europe, and Asian countries are still marginalized in the field of international heritage management. At present, it is urgent to tear the wrap of the discourse power of western international cultural heritage management and activate the motive force of the local culture of various countries and nationalities. If traditional culture is protected, managed and developed only in view of the economic value of "world heritage", Tai Chi will fall into the mire of degeneration and degeneration in human economic activities. In the context of world intangible heritage protection, the humanistic value system, social framework and cultural heritage management of Taijiquan can be traced, and the long-term compound interest and overlapping effect of cultural value of Taijiquan can be realized, so as to promote the transcendentally development of China's discourse power in international cultural heritage management. Therefore put forward: (1) through the legislation protection and creates taijiquan as a world heritage site sacred and inviolable, the taijiquan social concepts of isochronous constantly planning international risk management, structured management of cultural heritage, in a cyclical industry events to stimulate, innovation and extend taijiquan in the history of the international stage matrix. (2) to economic logic (exchange and control of resources, political logic (rights and the rule of management), the cultural logic (symbols and significance of bringing) cultural heritage management and supervision, in order to produce legal principle in this paper, the taijiquan implications of cultural heritage value, around to protect the diversity of tai chi be separated to rebuild social cultural space, the sense of identity. (3) standing in the grand and long-term vision of human civilization, in order to "meimei and" the cultural mentality of world culture, "harmony without uniformity" to the world civilization mutual appreciation, is cut with tai chi, sharing more generalized and the world civilization, Chinese civilization to achieve sustainable, can be perceived, visualization, renewable, cultural heritage, Feel the historical depth and the grand sense of human civilization. (4) communication mutual positive attitude to the world civilization, improve the voice in the non-material cultural heritage area, the continuous summary refine the heritage protection and management experience, to form a long-term effective mechanism of international cultural heritage management work, and explore the new path of non-material cultural heritage protection, in order to promote international intangible cultural heritage protection and management to provide constructive suggestions.